Beta-COF / GA composite adsorption material as well as preparation method and application thereof
By combining the β-ketoenamine covalent organic frame material with graphene aerogel to form β-COF/GA composite adsorbent, the problem of low micropore content of graphene aerogel adsorbent is solved, and the problem of significantly improved The adsorption capacity of phenol has achieved efficient removal of phenol in industrial wastewater and the multiple use of materials.
Patent Information
- Application Number
- CN202411328657.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-24
AI Technical Summary
The existing graphene aerogel adsorbent has low micropore content and a single type of surfactant functional groups, which leads to a low adsorption capacity of phenol, making it difficult to effectively remove phenol pollution in industrial wastewater.
The β-ketoenamine covalent organic frame material (β-COF) with high aqueous phase stability, high micropore content and high activity is combined with graphene aerogel, and the β-COF is used to recombinate the graphene aerogel through liquid phase reduction and self-assembly reaction. -COF is loaded on the graphene surface and pores to form a β-COF/GA composite adsorption material to improve its micropore content and adsorption activity.
The adsorption capacity of graphene aerogel-based adsorbent to phenol is significantly improved, and the efficient adsorption and removal of phenol molecules in the aqueous phase is achieved, and it has good regenerative properties and mechanical properties, which is suitable for industrial wastewater treatment.
Smart Images

Figure CN119281302A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water treatment adsorption materials, and relates to an adsorption material for adsorbing and removing phenol in wastewater, in particular to a carbon aerogel-based composite adsorption material. Background Art
[0002] There are a large number of organic pollutants in industrial wastewater, among which phenol molecules account for a large proportion. Phenol and its derivatives are carcinogenic and mutagenic to animals and humans. The discharge of phenol-containing wastewater poses a major threat to human health and environmental quality. Research and realization of the adsorption and removal of organic pollutants represented by phenol in industrial wastewater is of great significance for wastewater treatment, pollutant emission reduction, and ecological environmental protection.
[0003] As a bulk carbon material with a hierarchical porous structure, excellent mechanical properties and physicochemical stability, graphene aerogel not only has the advantages of low density, high strength, environmental friendliness, controllable structure and modifiable surface of carbon-based adsorbent materials, but also has the advantages of rapid mass transfer, high solid-liquid separation efficiency, low secondary pollution to the liquid phase environment system, good regeneration, etc. due to its three-dimensional spatial structure of macroscopic blocks, large specific surface area and rich pore structure, making it a highly potential adsorbent material in the field of industrial wastewater dephenolization. However, the single-component graphene aerogel adsorbent has a low micropore content, a single type of surface active functional groups and a limited number, resulting in a low adsorption capacity for phenol.
[0004] By adopting a high water phase stability, high micropore content, high activity β -Keto-enamine covalent organic framework materials ( β -COF) is compounded with graphene aerogel to improve the micropore content and adsorption activity of the adsorption material, and to construct β -COF / graphene composite aerogel bulk adsorption material ( β -COF / GA), which has good research and development value for improving the adsorption capacity of graphene aerogel-based adsorbents for phenol and promoting the actual application of dephenolization in industrial wastewater. Summary of the invention
[0005] The object of the present invention is to provide a β -COF / GA composite adsorption material and its preparation method to effectively improve the phenol adsorption capacity of graphene aerogel-based adsorbent.
[0006] In order to achieve the above-mentioned purpose of the invention, the present invention β -COF / GA composite adsorption material uses graphene oxide as a carbon precursor and a reinforcing phase β -COF blended to form an aqueous solution system, adding reducing agent ammonium citrate to carry out liquid phase reduction self-assembly reactionβ -COF loaded on the surface and pores of reduced graphene aerogel β -Adsorption material with a mass ratio of COF to graphene oxide of 1:5 to 15.
[0007] The present invention β -COF / GA composite adsorption material uses graphene oxide as a carbon precursor. On the one hand, graphene oxide can self-assemble and connect through a hydrothermal reduction reaction to form a three-dimensional bulk graphene aerogel with an ideal pore structure and mechanical properties; on the other hand, since graphene oxide is a large-sized two-dimensional structure and contains rich oxygen-containing functional groups, the graphene aerogel obtained with it as a precursor can easily form π-π interactions and hydrogen bonds with phenol, which can improve its adsorption activity and adsorption capacity for phenol.
[0008] The present invention β -Reinforcement phase in COF / GA composite adsorption materials β -COF is a covalent organic framework material with high water phase stability, rich micropore content, and abundant nitrogen and oxygen functional groups, which can interact with phenol and attract the appropriate amount of β -COF is loaded on the surface and pore structure of graphene aerogel, which can effectively improve the overall micropore content and adsorption activity of the adsorption material.
[0009] The present invention is carried out by β -COF and graphene oxide were mixed in aqueous solution, and the reducing agent ammonium citrate was added to carry out liquid phase self-assembly reaction, achieving the appropriate amount of β -COF loading on the surface and pore structure of graphene aerogels resulted in a block with rich microporous structure and high adsorption activity β -COF / GA composite adsorption material can be used for efficient adsorption and removal of phenol molecules in aqueous solution.
[0010] Furthermore, the present invention also provides a suitable β - Preparation method of COF / GA composite adsorption material:
[0011] 1) 1,3,5-triformylphloroglucinol and aniline compounds are used as reaction raw materials, water is used as solvent and p-toluenesulfonic acid is added to promote the dissolution of the raw materials in water, and a hydrothermal reaction is carried out to connect the raw materials to form a six-membered ring structural unit to obtain a water-stable powder. β -COF;
[0012] 2) β -COF is the reinforcing phase, graphene oxide is the carbon precursor, and ammonium citrate is the reducing agent. The mixture is dissolved in water to carry out a liquid phase reduction self-assembly reaction, so that the graphene oxide is reduced and self-assembled. β-COF loading is formed on the graphene surface and in the pores β -COF / graphene composite hydrogel, obtained by freeze drying β -COF / GA composite adsorption material.
[0013] Wherein, the aniline compound can be p-phenylenediamine or benzidine.
[0014] Specifically, it is preferred that the molar ratio of 1,3,5-triformylphloroglucinol to the aniline compound is 1:1-2, and the molar ratio of 1,3,5-triformylphloroglucinol to p-toluenesulfonic acid is 1:1-2.
[0015] Furthermore, the hydrothermal reaction is specifically carried out at a constant temperature of 100-150° C. for 18-36 hours.
[0016] Specifically, it is preferred β The mass ratio of -COF to graphene oxide is 1:5-15, and the mass ratio of graphene oxide to ammonium citrate is 1:3-7.
[0017] Furthermore, the liquid phase reduction self-assembly reaction is specifically a constant temperature hydrothermal reaction at 100-150° C. for 8-15 hours.
[0018] Furthermore, β The COF / graphene composite hydrogel is frozen below -80°C to solidify the water, and then freeze-dried to sublime the solid water to obtain the β -COF / GA composite adsorption material.
[0019] The present invention utilizes high water phase stability, high micropore content, high activity β -COF as a reinforcing phase improves the problems of low micropore content and low adsorption activity of existing graphene aerogel adsorption materials.
[0020] The present invention prepares β -COF / GA composite adsorption material is a black cylindrical block adsorption material, which is interconnected by graphene sheets. The graphene sheets and stacked channels are loaded with a proper amount of β -COF nanoparticles have rich microporous structures and high adsorption activity, which can achieve efficient adsorption and removal of phenol molecules in the aqueous phase and can be used multiple times after elution and regeneration.
[0021] The present invention β -COF / GA composite adsorption material has a simple preparation method, low cost, convenient operation and strong practicality, and can be widely used in adsorption, separation, detection and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The product of Example 1β -COF(a) and β -Field emission scanning electron microscopy of COF / GA composite adsorbent (b) and β - Actual photo of COF / GA composite adsorbent material (c).
[0023] Figure 2 The product of Example 1 β -COF and β -XRD spectrum (a) and TG curve (b) of COF / GA composite adsorbent material.
[0024] Figure 3 The product of Example 1 β -COF and β -COF / GA composite adsorbent material adsorption kinetics curves for phenol (a) and β -Adsorption regeneration performance diagram of COF / GA composite adsorbent material (b).
[0025] Figure 4 The comparative example product GA (a) β -COF / 15GA (b) and β -Scanning electron microscope image of COF / 3GA (c).
[0026] Figure 5 yes β -COF, β -COF / GA, GA, β -COF / 15GA and β -Comparison of the maximum adsorption performance of COF / 3GA for phenol.
[0027] Figure 6 These are field emission scanning electron images of the products of Example 4, triazine COF (a) and triazine COF / GA composite aerogel (b). Implementation
[0028] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.
[0029] The production processes, experimental methods or detection methods involved in the embodiments and comparative examples of the present invention are all conventional methods in the prior art unless otherwise specified, and their names and / or abbreviations are all conventional names in the field and are very clear and unambiguous in the relevant application fields. Technicians in the field can understand the conventional process steps based on the names and apply the corresponding equipment to implement them according to conventional conditions or the conditions recommended by the manufacturer.
[0030] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art.
[0031] The present invention first provides a suitable covalent organic framework material β -COF preparation method:
[0032] It is synthesized from 1,3,5-triformylphloroglucinol and aniline compounds (such as p-phenylenediamine and benzidine). β The reaction raw materials of -COF are water-based solvents, and p-toluenesulfonic acid is added to promote the dissolution of the two raw materials in water, and then a hydrothermal reaction is carried out to connect the two raw materials to form a six-membered ring structural unit, and then necessary washing and vacuum drying are carried out to obtain a water-stable powder. β -COF.
[0033] The purity of the raw materials 1,3,5-triformylphloroglucinol and aniline compounds used is above 97%, and p-toluenesulfonic acid is analytical grade.
[0034] Specifically, the molar ratio of the raw material 1,3,5-triformylphloroglucinol to the aniline compound is preferably 1:1-2, the molar ratio of 1,3,5-triformylphloroglucinol to p-toluenesulfonic acid is preferably 1:1-2, and the molar ratio of 1,3,5-triformylphloroglucinol to the solvent water is preferably 1:7000-8000.
[0035] More specifically, the dissolution order of various raw materials for the hydrothermal reaction is preferably: first add p-toluenesulfonic acid to water, and dissolve it by ultrasonic at room temperature for 3 to 5 minutes; then add aniline compounds and dissolve them in the p-toluenesulfonic acid aqueous solution, and dissolve them by ultrasonic at room temperature for 10 to 15 minutes; finally add 1,3,5-triformylphloroglucinol and dissolve it in the above mixed solution system, and dissolve it by ultrasonic at room temperature for 30 to 40 minutes. More preferably, a continuous stirring state is maintained during the above dissolution process to ensure that various raw materials are fully and evenly blended.
[0036] Furthermore, the mixed solution is placed in a polytetrafluoroethylene-lined hydrothermal reactor, which is sealed and placed in an oven. The temperature is raised from room temperature to 100-150° C., and a constant temperature hydrothermal reaction is performed for 18-36 hours to connect 1,3,5-triformylphloroglucinol with the aniline compound to form a six-membered ring structure unit.
[0037] Furthermore, the hydrothermal reaction product is washed sufficiently with acetone and water in sequence to remove unreacted raw materials in the product.
[0038] Preferably, the number of times of washing with acetone is 3 to 5 times, and the number of times of washing with water is 6 to 10 times.
[0039] Furthermore, the washed product is placed in a vacuum drying oven at 60°C and dried for 2 to 4 days to remove the residual solvent, thereby obtaining a highly crystalline solid powder. β -COF.
[0040] Secondly, the present invention also provides a β -COF β -COF / GA composite adsorption material preparation method:
[0041] As mentioned β -COF is used as the reinforcement phase, graphene oxide is used as the carbon precursor, and ammonium citrate is used as the reducing agent. The liquid phase reduction self-assembly reaction is carried out in water. β -COF is attached to the reduced graphene surface or in the pores formed by the assembly of sheets, and the appropriate amount of β -COF loading on the surface and pores of graphene aerogels, β -COF / GA composite adsorption material.
[0042] The present invention preferably uses graphene oxide with a thickness of no more than 1 µm and a single-layer sheet diameter of 0.2 to 10 µm as a carbon precursor, and preferably the purity of ammonium citrate is above 98.5%.
[0043] Specifically, a graphene oxide aqueous solution, an ammonium citrate aqueous solution and β After the -COF solid powder is fully blended at room temperature, a liquid phase reduction self-assembly reaction is carried out to reduce the graphene oxide and produce self-assembly behavior, while the loaded β -COF, formed β -COF / graphene composite hydrogel, dialyzed in ethanol aqueous solution and freeze-dried to form β -COF / GA composite adsorption material.
[0044] More specifically, the concentration of the graphene oxide aqueous solution is 3 to 5 g / L, the concentration of the ammonium citrate aqueous solution is 50 to 80 g / L, and the mass ratio of graphene oxide to ammonium citrate is preferably 1:3 to 7, preferably β The mass ratio of -COF to graphene oxide is 1:5-15.
[0045] More specifically, the present invention preferably adds graphene oxide to water, and ultrasonically disperses it at room temperature for 1 to 2 hours; then adds β -COF, continue ultrasonic dispersion for 10 to 15 minutes; then add the ammonium citrate aqueous solution to the reaction system at a rate of 3 to 5 drops per second. After the addition is complete, stir the mixed reaction system at 25°C for 10 to 15 minutes to ensure that the graphene oxide, β-COF and ammonium citrate are mixed uniformly in aqueous solution.
[0046] Furthermore, the liquid phase reduction self-assembly reaction is specifically to place the above mixed solution in a hydrothermal reactor lined with polytetrafluoroethylene, seal it and place it in an oven, raise the temperature from room temperature to 100-150°C, and perform a constant temperature hydrothermal reaction for 8-15h to reduce and encapsulate the graphene oxide. β -COF, formed by self-assembly β -COF / graphene composite hydrogel.
[0047] Furthermore, an ethanol aqueous solution having a volume ratio of ethanol to water of preferably 4 to 8:1 is prepared and placed β -COF / graphene composite hydrogel was dialyzed to remove unreacted raw materials.
[0048] The specific number of dialysis sessions is 4 to 6 times, and the dialysis time is 2 to 3 days.
[0049] Furthermore, the dialysis β -COF / graphene composite hydrogel was placed in a freezer below -80°C. β The water in the -COF / graphene composite hydrogel was frozen and solidified, and then freeze-dried in a freeze drying oven at -80°C for 3 to 5 days. β After the solid water in the COF / graphene composite hydrogel is sublimated, β -COF / GA composite adsorption material. Example
[0050] Example 1
[0051] Weigh 64 mg of p-toluenesulfonic acid into a glass bottle containing 5 mL of deionized water, and sonicate for 3 min at 25° C. to fully dissolve it to obtain an aqueous p-toluenesulfonic acid solution.
[0052] Weigh 6 mg of p-phenylenediamine into the above-mentioned p-toluenesulfonic acid aqueous solution, and perform ultrasonic treatment at 25° C. for 10 min to fully dissolve it to obtain a mixed aqueous solution.
[0053] 7.8 mg of 1,3,5-triformylphloroglucinol was weighed and added to the mixed aqueous solution. The mixture was ultrasonicated for 30 min and manually stirred continuously to be fully and evenly blended to obtain a blended solution.
[0054] The mixed solution was transferred to a hydrothermal reactor lined with polytetrafluoroethylene, sealed and placed in an oven, and heated to 120°C for constant temperature hydrothermal reaction for 24 hours to allow 1,3,5-triformylphloroglucinol and p-phenylenediamine to fully react and connect to form a six-membered ring structural unit.
[0055] After the hydrothermal reaction product was cooled, it was washed with acetone for 3 times, then washed with water for 6 times, and dried in a vacuum drying oven at 60°C for 3 days to remove the residual solvent, thereby obtaining a solid powder. β -COF.
[0056] 0.24 g of graphene oxide was weighed into a beaker containing 80 mL of deionized water, and ultrasonicated for 1.5 h at 25° C. to uniformly disperse the graphene oxide to obtain a graphene oxide dispersion.
[0057] Weigh 1 g of ammonium citrate into 20 mL and dissolve it completely by ultrasonication at 25°C for 10 min to obtain an ammonium citrate aqueous solution.
[0058] Measure 12 mL of graphene oxide dispersion into a cylindrical glass bottle and add 4 mg of the above β -COF powder, and then add 3.6mL of ammonium citrate aqueous solution at a rate of 3 drops per second. After the addition is completed, the mixed reaction system is stirred at 25°C for 15 minutes to ensure that the graphene oxide, β -COF and ammonium citrate are mixed uniformly in aqueous solution.
[0059] The mixed solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor, sealed and placed in an oven, heated to 120°C for a constant temperature hydrothermal reaction for 12 hours to reduce and encapsulate the graphene oxide. β -COF, formed by self-assembly β -COF / graphene composite hydrogel.
[0060] Will get β The -COF / graphene composite hydrogel was placed in an 85% ethanol aqueous solution for dialyzing, and the dialysate was changed every 12 hours. After changing it 4 times, it was repeatedly rinsed with clean water to remove the unreacted raw materials, and then placed in a freezer below -80°C for freezing and solidification, and then placed in a freeze drying box and freeze-dried at a temperature below -80°C for 3 days. β -Solid water sublimation in COF / graphene composite hydrogel to obtain β -COF and graphene oxide mass ratio of 1:9 β -COF / GA composite adsorption material.
[0061] Figure 1 The above preparation β -COF(a) and β -Field emission scanning electron microscopy of COF / GA composite adsorbent (b) and β -Actual photo of COF / GA composite adsorption material (c). It can be seen β -COF microstructure is sea urchin-like, and the obtained β-COF / GA composite adsorption material is formed by stacking and connecting larger graphene sheets, and a large number of β -COF. Actual photos β -COF / GA composite adsorption material is a black cylinder with a cross-sectional diameter of 1 cm and a height of 1.5 cm. It can be directly put into the solution for adsorption operation. The adsorption process is more convenient and helps to recycle the adsorption material.
[0062] Figure 2 of β -COF and β -XRD spectrum of COF / GA composite adsorbent (a), β -COF in 2 θ The characteristic diffraction peak appears at 4.5°. β -COF / GA composite adsorption material is 2 θ Diffraction peaks appear at 4.5° and 26°, corresponding to β -COF characteristic peak and carbon package peak confirm β -COF and GA composite. In addition, it can be seen from the TG curve (b) that β The total thermogravimetric loss rate of -COF at 800℃ is 48.5%. As GA has good thermal stability as a carbon material, β -COF / GA composite adsorbent material has a total thermogravimetric loss rate of only 25.0% at 800℃, and due to β Thermal decomposition of -COF makes β -The thermal gravimetric curve of COF / GA composite adsorbent material decreases rapidly in the range of 450-500℃.
[0063] Figure 3 Given β -COF and β -COF / GA composite adsorbent material adsorption kinetics curves of phenol (a) and β -COF / GA composite adsorbent material adsorption regeneration performance diagram (b). It can be seen that under the same adsorption conditions in (a), β The saturated adsorption capacity of -COF for phenol was only 28.15 mg g -1 , mainly due to its high microporous structure and the attraction of nitrogen and oxygen functional groups to phenol; and after it is used as a reinforcing phase and combined with GA, β The saturated adsorption capacity of phenol by COF / GA composite adsorbent increased to 55.91 mg g -1 In addition, due to the block β-COF / GA composite adsorbent material has good mechanical properties and can be recycled many times. In (b), after the first adsorption saturation, after 5 elution regeneration-phenol adsorption cycle tests, the saturated adsorption amount of phenol can still be maintained at 94.27% of the first saturated adsorption value.
[0064] In addition, in Table 1 β -COF and β -Comparison of specific surface area and pore structure data of COF / GA composite adsorption materials, β -COF has a very high micropore content, and its micropore specific surface area S micro The value reaches 929.240m 2 g -1 , the rich microporous structure makes the corresponding β -COF / GA composite adsorption material also has a certain microporous structure. S micro The value is 148.312m 2 g -1 , which is beneficial to the improvement of the material's adsorption capacity of phenol.
[0065] Comparative Example 1
[0066] 0.24 g of graphene oxide was weighed into a beaker containing 80 mL of deionized water, and ultrasonicated for 1.5 h at 25° C. to uniformly disperse the graphene oxide to obtain a graphene oxide dispersion.
[0067] Weigh 1 g of ammonium citrate into 20 mL and dissolve it completely by ultrasonication at 25°C for 10 min to obtain an ammonium citrate aqueous solution.
[0068] 12 mL of graphene oxide dispersion was measured and placed in a cylindrical glass bottle, and 3.6 mL of ammonium citrate aqueous solution was added dropwise at a rate of 3 drops per second. After the addition was completed, the mixed reaction system was stirred at 25° C. for 15 min to ensure that the graphene oxide and ammonium citrate were evenly mixed in the aqueous solution.
[0069] The mixed solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor, sealed and placed in an oven, and heated to 120° C. for constant temperature hydrothermal reaction for 12 h, so that the graphene oxide was reduced and self-assembled to form a graphene hydrogel.
[0070] The obtained graphene hydrogel was placed in an 85% ethanol aqueous solution for dialysis, and the dialysate was changed every 12 hours. After changing it 4 times, it was repeatedly rinsed with clean water to remove the unreacted raw materials, and then placed in a freezer below -80°C for freezing and solidification, and then placed in a freeze drying box and freeze-dried at a temperature below -80°C for 3 days to sublimate the solid water in the graphene hydrogel to obtain β -COF bulk graphene adsorption material, denoted as GA.
[0071] The scanning electron microscope image of GA is as follows Figure 4 As shown in (a), the interior of the adsorbent material is formed by stacking and connecting relatively large, smooth and flat graphene sheets, and the graphene surface and sheets are assembled to form a rich stepped pore structure. Such a structure can ensure that the adsorbent material is in a block shape and has good mechanical properties. However, according to the specific surface area and pore structure data of GA in Table 1, it can be seen that it lacks a microporous structure.
[0072] from Figure 5 It can be seen that under the same adsorption conditions, the saturated adsorption capacity of GA on phenol is only 19.74 mg g -1 , mainly due to its π–π interaction and hydrogen bonding with phenol.
[0073] Figure 5 In Example 1, β The saturated adsorption capacity of -COF is only 28.15 mg g -1 , but after combining the two in a suitable ratio, β The saturated adsorption capacity of phenol by COF / GA composite adsorbent increased significantly to 55.91 mg g -1 , indicating that β The introduction of -COF can effectively improve the overall micropore content and adsorption activity of the adsorption material.
[0074] Example 2
[0075] Weigh 67 mg of p-toluenesulfonic acid into a glass bottle containing 5 mL of deionized water, and sonicate for 5 min at 25° C. to fully dissolve it to obtain an aqueous p-toluenesulfonic acid solution.
[0076] Weigh 6.5 mg of p-phenylenediamine into the above-mentioned p-toluenesulfonic acid aqueous solution, and perform ultrasonic treatment at 25° C. for 13 min to fully dissolve it to obtain a mixed aqueous solution.
[0077] 8 mg of 1,3,5-triformylphloroglucinol was weighed and added to the mixed aqueous solution. The mixture was ultrasonicated for 40 min and manually stirred to be fully and evenly blended to obtain a blended solution.
[0078] The mixed solution was transferred to a hydrothermal reactor lined with polytetrafluoroethylene, sealed and placed in an oven, and heated to 125°C for constant temperature hydrothermal reaction for 25 hours to allow 1,3,5-triformylphloroglucinol and p-phenylenediamine to fully react and connect to form a six-membered ring structural unit.
[0079] After the hydrothermal reaction product was cooled, it was washed with acetone 4 times, then washed with water 5 times, and dried in a vacuum drying oven at 60°C for 2.5 days to remove the residual solvent to obtain a solid powder. β -COF.
[0080] Prepared as above β -COF powder was used to prepare composite adsorption material according to the method of Example 1 to obtain β -COF and graphene oxide mass ratio of 1:9 β -COF / GA composite adsorption material.
[0081] After testing, its properties and phenol adsorption performance are consistent with those of the composite adsorption material in Example 1.
[0082] Example 3
[0083] 0.27 g of graphene oxide was weighed into a beaker containing 80 mL of deionized water, and ultrasonicated for 1.6 h at 25° C. to uniformly disperse the graphene oxide to obtain a graphene oxide dispersion.
[0084] Weigh 1.1 g of ammonium citrate into 20 mL and sonicate for 12 min at 25° C. to fully dissolve it to obtain an ammonium citrate aqueous solution.
[0085] 12 mL of graphene oxide dispersion was measured and placed in a cylindrical glass bottle, and 4 mg of the β -COF powder, and then 3.8 mL of ammonium citrate aqueous solution was added at a rate of 4 drops per second. After the addition was completed, the mixed reaction system was stirred at 25 ° C for 13 minutes to ensure that the graphene oxide, β -COF and ammonium citrate are mixed uniformly in aqueous solution.
[0086] The mixed solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor, sealed and placed in an oven, heated to 130°C for 15 hours to reduce and encapsulate the graphene oxide. β -COF, formed by self-assembly β -COF / graphene composite hydrogel.
[0087] Will get β The -COF / graphene composite hydrogel was placed in a 75% ethanol aqueous solution for dialysis, and the dialysis solution was changed every 12 hours. After 5 changes, it was repeatedly rinsed with clean water to remove the unreacted raw materials, and then placed in a freezer below -80°C for freezing and solidification, and then placed in a freeze drying box and freeze-dried at a temperature below -80°C for 2 days. β -Solid water sublimation in COF / graphene composite hydrogel to obtain β -COF and graphene oxide mass ratio of 1:9 β -COF / GA composite adsorption material.
[0088] After testing, its properties and phenol adsorption performance are consistent with those of the composite adsorption material in Example 1.
[0089] Example 4
[0090] In addition to β Except that the amount of -COF powder was reduced from 4 mg to 2.4 mg, the other reaction conditions were exactly the same as those in Example 1 to prepare β The bulk composite adsorption material with a mass ratio of -COF to graphene oxide of 1:15 is denoted as β -COF / 15GA.
[0091] β -Scanning electron microscope image of COF / 15GA Figure 4 As shown in (b), we can see that due to only a small amount of β -COF was added to the composite reaction system. β -COF / 15GA has only a few β -COF is loaded on the surface of GA.
[0092] Table 1 β -The specific surface area and pore structure data of COF / 15GA are compared with those of GA due to the high micropore content. β -COF is added, so β -COF / 15GA has a higher micropore content than GA. S micro The value is 93.554m 2 g -1 The same as the product of Example 1 β -COF / GA comparison, due to the loading of Example 1 β -COF has more volume, β -The micropore content of COF / 15GA is less than β -COF / GA.
[0093] Further based on Figure 5 It can be seen that under the same adsorption conditions, β The saturated adsorption capacity of -COF / 15GA for phenol was 45.41 mg g -1 , higher than the uncompounded β -COF and GA adsorption, but due to β -COF added in a small amount, its adsorption value is still slightly lower than that of the product in Example 1 β -Phenol adsorption value of COF / GA.
[0094] Comparative Example 2
[0095] In addition to β Except that the amount of -COF powder was increased from 4 mg to 12 mg, the other reaction conditions were exactly the same as those in Example 1 to prepare β-COF and graphene oxide mass ratio of 1:3 bulk composite adsorption material, denoted as β -COF / 3GA.
[0096] β -Scanning electron microscope image of COF / 3GA Figure 4 As shown in (c), it can be seen that due to the excess β -COF was added to the composite reaction system. β -A large number of β -COF accumulates and aggregates on the surface of GA, causing the pores of GA to be stretched and destroyed.
[0097] Table 1 β -COF / 3GA specific surface area and pore structure data are the same as GA and β Compared with COF / 15GA, due to the high micropore content β -COF is more, making β -COF / 3GA has a higher micropore content than GA and β -COF / 15GA, S micro The value is 109.565m 2 g -1 .but β -COF / 3GA has less micropore content than the product of Example 1 β -COF / GA, this is because although β -COF / 3GA loads more β -COF, but β -COF loading is too much in the same area of the aerogel, resulting in rigid one-dimensional pores. β -COF accumulation is serious and the aerogel pore structure is destroyed. The damage of these structures also makes Figure 5 middle β The saturated adsorption capacity of phenol on -COF / 3GA decreased to 25.64 mg g -1 .
[0098]
[0099] Therefore, based on the above characterization data, β -COF / GA composite adsorption material β The -COF content should not be too high, and the present invention limits the maximum mass ratio of the -COF content to graphene oxide to 1:5.
[0100] Comparative Example 4
[0101] 1 mL of ethanol and 1 mL of 1,2-dichlorobenzene solution were mixed in a glass bottle to obtain a mixed solution.
[0102] 20.5 mg of 4,4',4''-(1,3,5-triazine-2,4,6-triyl)triphenylamine and 11.6 mg of terephthalaldehyde were weighed into the above mixed solution, 0.2 mL of 6 M acetic acid solution was added dropwise, and ultrasonication was performed for 15 min.
[0103] The mixed solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor, sealed and placed in an oven, and heated to 120°C for a constant temperature hydrothermal reaction for 72 hours.
[0104] After the hydrothermal reaction product was cooled, it was washed three times with ethanol and three times with tetrahydrofuran, respectively, and dried in a vacuum drying oven at 45° C. for 3 days to remove the solvent, thereby obtaining a solid powder triazine COF.
[0105] The triazine COF obtained above was used to replace the β -COF powder, and the other parts were exactly the same as those in the preparation of the composite adsorption material in Example 1, to obtain a bulk triazine COF / GA composite aerogel with a mass ratio of triazine COF to graphene oxide of 1:9.
[0106] Figure 6 The field emission scanning electron microscope images of the triazine COF (a) and triazine COF / GA composite aerogel (b) prepared above can be seen. It can be seen that triazine COF is agglomerated particles with a regular microstructure, while the microstructure of the triazine COF / GA composite aerogel produced after the composite hydrothermal reaction is more similar to the morphological structure of the product GA in Comparative Example 1, which is composed of stacked graphene sheets. It is difficult to observe triazine COF particles on the graphene sheets and in the pore structure. This is because the stability of triazine COF in the aqueous phase is relatively poor, so that during the composite hydrothermal process, as the graphene hydrogel is formed, triazine COF decomposes, resulting in the inability of the two to be composited.
[0107] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.
Claims
1. A β -COF / GA composite adsorption material is based on graphene oxide as a carbon precursor and a reinforcing phase. β -COF blended to form an aqueous solution system, adding reducing agent ammonium citrate to carry out liquid phase reduction self-assembly reaction β -COF loaded on the surface and pores of reduced graphene aerogel β -Adsorption material with a mass ratio of COF to graphene oxide of 1:5 to 15.
2. The method according to claim 1 β -The preparation method of COF / GA composite adsorption material is characterized by: 1) 1,3,5-triformylphloroglucinol and aniline compounds are used as reaction raw materials, water is used as solvent and p-toluenesulfonic acid is added to promote the dissolution of the raw materials in water, and a hydrothermal reaction is carried out to connect the raw materials to form a six-membered ring structural unit to obtain a water-stable powder. β -COF; 2) β -COF is the reinforcing phase, graphene oxide is the carbon precursor, and ammonium citrate is the reducing agent. The mixture is dissolved in water to carry out a liquid phase reduction self-assembly reaction, so that the graphene oxide is reduced and self-assembled. β -COF loading is formed on the graphene surface and in the pores β -COF / graphene composite hydrogel, obtained by freeze drying β -COF / GA composite adsorption material.
3. According to claim 2 β -COF / GA composite adsorption material preparation method, characterized in that The aniline compound is p-phenylenediamine or benzidine.
4. according to claim 2 β -COF / GA composite adsorption material preparation method, characterized in that The molar ratio of 1,3,5-triformylphloroglucinol to the aniline compound is 1:1-2, and the molar ratio of 1,3,5-triformylphloroglucinol to p-toluenesulfonic acid is 1:1-2.
5. According to claim 2 β -COF / GA composite adsorption material preparation method, characterized in that The hydrothermal reaction is carried out at a constant temperature of 100 to 150° C. for 18 to 36 hours.
6. According to claim 2 β -COF / GA composite adsorption material preparation method, characterized in that < i>The mass ratio of β-COF to graphene oxide is 1:5-15, and the mass ratio of graphene oxide to ammonium citrate is 1:3-7.
7. According to claim 2 β -COF / GA composite adsorption material preparation method, characterized in that The liquid phase reduction self-assembly reaction is a constant temperature hydrothermal reaction at 100-150° C. for 8-15 hours.
8. The method according to claim 1 β -Application of COF / GA composite adsorbent as adsorption and removal agent for phenol molecules in aqueous solution.
Citation Information
Patent Citations
Preparation method of COF / GO (covalent organic framework / graphene oxide) adsorbent and application
CN107970894A
Preparation method of graphene composite aerogel
CN108940141A
Preparation method of graphene-based composite aerogel material for adsorbing heavy metal ions
CN117920155A